2010
DOI: 10.1002/etc.263
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at bioaccumulation of petroleum hydrocarbon mixtures in aquatic worms

Abstract: Petroleum hydrocarbons (oils) are ubiquitous in the aquatic environment, and adequate risk assessment is thus essential. Bioaccumulation plays a key role in risk assessment, but the current knowledge on bioaccumulation of oils is limited. Therefore, this process was studied in detail, using the aquatic worm, Lumbriculus variegatus, and 14 field-contaminated sediments. The main focus during the present study was on uptake kinetics, the relationship between oil boiling point fraction and uptake, and effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 37 publications
3
39
3
Order By: Relevance
“…Initially the limit identified in Equation 1 was parameterized at log K OW of 6 [9,[40][41][42][43], which effectively reduced the bioavailability of more hydrophobic components while allowing fractional contribution to overall toxicity of the substance to be included in P TU calculations [44][45][46]. This nonlinear partitioning behavior may reflect the impact of low solubility and slow toxicokinetics [47] or other competing processes that limit accumulation in the target lipid for these low-solubility constituents.…”
Section: Modeling Analysismentioning
confidence: 99%
“…Initially the limit identified in Equation 1 was parameterized at log K OW of 6 [9,[40][41][42][43], which effectively reduced the bioavailability of more hydrophobic components while allowing fractional contribution to overall toxicity of the substance to be included in P TU calculations [44][45][46]. This nonlinear partitioning behavior may reflect the impact of low solubility and slow toxicokinetics [47] or other competing processes that limit accumulation in the target lipid for these low-solubility constituents.…”
Section: Modeling Analysismentioning
confidence: 99%
“…Most studies on crude oil spills have focused on polycyclic aromatic hydrocarbons (PAHs), and have shown that these contaminants caused detrimental effects on various aquatic organisms [2][3][4][5][6]. Conversely, other constituents in the oil matrix, which were commonly referred to as an unresolved complex mixture (UCM) were less studied [7][8][9][10]. The UCM was composed of weathered oils, which originated from natural and/or anthropogenic sources, and was first recognized as the "hump" in the quantification of petroleum-contaminated sediment samples using gas chromatography (GC) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, have showed that the UCM constituents in sediment not only accumulated in benthic organisms, but also caused sub-lethal effects to these organisms [7][8][9][10][11]15]. For example, UCM contributed to the overall toxic effects of oils to the marine amphipod Corophium volutator and its contribution was separate from the PAHs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation rates were greatest for the lowest-boiling-point distillate (F2) and progressively decreased as the boiling point range of the distillate increased (Table 2), as noted by others [23]. This likely is due to a decrease in the bioavailability of oil constituents resulting from changes in sorption and water solubility as the boiling point range for hydrocarbons increases [2,25].…”
Section: Accumulation and Elimination Of F2 F3a And F3bmentioning
confidence: 62%